1998
DOI: 10.1111/j.1469-7793.1998.267bo.x
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of pyrogen‐induced tumour necrosis factor by its type 1 soluble receptor in guinea‐pigs: effects on fever and interleukin‐6 release

Abstract: A soluble form of the tumour necrosis factor (TNF) type 1 receptor (referred to as TNF binding protein, TNF‐bp) at a dose of 1 mg per animal, or an equivalent volume of solvent, was injected together with 10 μg kg−1 lipopolysaccharide (LPS) or 50 μg kg−1 muramyl‐dipeptide (MDP) directly into the arterial circulation of guinea‐pigs and the effects on circulating TNF or interleukin‐6 (IL‐6) and on abdominal temperature were studied. At 15 or 60 min after injection, LPS‐induced and MDP‐induced circulating TNF was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
54
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 33 publications
2
54
1
Order By: Relevance
“…The fever, in this case, was biphasic. The shape of the fever curve resembled a curve after systemic treatment with LPS (32,34). Although the local formation of PGE 2 within the subcutaneous chamber was similar in response to both LPS doses (Fig.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The fever, in this case, was biphasic. The shape of the fever curve resembled a curve after systemic treatment with LPS (32,34). Although the local formation of PGE 2 within the subcutaneous chamber was similar in response to both LPS doses (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…lipopolysaccharide; febrile response; prostaglandin E 2; cyclooxygenase-2; immune system-to-brain communication MOST EXPERIMENTAL STUDIES employing bacterial lipopolysaccharide (LPS) to induce fever use a systemic route of administration, such as intraperitoneal, intravenous, or intra-arterial injections of the pyrogen. These treatments result in a generalized systemic inflammatory response, which is accompanied by increased measurable amounts of proinflammatory cytokines and LPS in the circulation (10,14,17,28,32). To study a cytokine release within a local area of inflammation, experimental models have been introduced in which LPS is administered locally, rather than systemically, into a subcutaneous air pouch in rats (8,22,23) or a subcutaneously implanted artificial Teflon chamber in guinea pigs (29,30,34).…”
mentioning
confidence: 99%
“…Administration of a dimeric polyethylene glycol-linked form of the type 1 soluble receptor of TNF, a neutralizing TNF-binding protein, abolishes LPSinduced circulating bioactive TNF and causes a significant attenuation of the second phase of the febrile response (17). Intraperitoneal injection of 30 µg/kg LPS induces a similar biphasic fever in guinea pigs (lower panel of Figure 1).…”
mentioning
confidence: 70%
“…mRNA for these cytokines was detected early during the infection process, with peak IL-1␤ mRNA expression preceding that of TNF-␣ and occurring at the same time that we observed an increase in body temperature, between 25 and 35 days postinfection, in nonvaccinated animals. In other studies using the guinea pig as an animal model, others have demonstrated the dependence of the fever response on such cytokines such as IL-1␤, TNF-␣, and IL-6 (27), and thus, it appears plausible that these cytokines mediate an increase in body temperature during infection with M. tuberculosis.…”
Section: Discussionmentioning
confidence: 99%